Spatial Variability of Soil Organic Carbon Stock in Gurje Subwatershed, Hadiya Zone, Southern Ethiopia - Temesgen Addise; Bobe Bedadi; Alemayehu Regassa; Lemma Wogi; Samuel Feyissa (Applied and Environmental Soil Science)
Soil organic carbon contents are expected to vary from place to place because of variation in soil properties. However, the extent of variability has not been explored in the study area. This study has, therefore, been initiated to assess the spatial variability of soil organic carbon stock in Gurje subwatershed Hadiya Zone, Southern Ethiopia. A total of 40 randomly predefined sampling points were identified for soil sampling using GIS and a total of 80 composite soil samples and 80 core samples were collected from those points at two sampling soil depths (0–20 cm and 20–40 cm). The ordinary kriging (OK) method was used as a geostatistical tool and applied to model the spatial variability of soil organic carbon in this study. With respect to soil depth, the coefficient of variation (CV%) for SOC and SOCS varied from 40.87 to 51.36%, which indicated moderate variability in the study area. For the land use types, the CV% varied from 7.94 to 42.06%, indicating low to moderate variability for the variables in the study area. The exponential semivariogram model described the spatial structure of SOC at 0–20 cm depth while the spherical one was used for SOCS. Moreover, the exponential model was best suited for SOCS at a soil depth of 20–40 cm, while the circular model was appropriate for SOC at this depth. The nugget/sill ratio (C0/C0 + C) of SOC and SOCS varied from nil to 15.58, reflecting a strong spatial dependence, which could be mainly due to the influence of intrinsic factors (e.g., natural variations in soils) in the study area. Overall, the spatial distributions of SOC and SOCS were higher in the northwestern and eastern parts of the subwatershed.